Work conditions in transition : a study of work culture and gender issues in a changing technical context - Johansson, Jan; Abrahamsson, Lena (Luleå tekniska universitet, Arbetsvetenskap, 2007)
Over a period of 50 years at Kiruna iron ore mine we can see a transformation of work from underground to remote control at surface level. What characterised the old underground face work was the close relation between man and the hard rock based on hard physical work under dangerous condition. Nowadays the face workers are located up in the sky on level 7 in an office building close to the mine. The contact with the hard rock goes through machines controlled by remote technology. The traditional workplace culture and the macho style have been challenged. The modern technology has created a new type of work, when it comes to competence and knowledge as well as workload. The purpose of the paper is to reflect on the upcoming, and in many aspects already evident, knowledge transformation - from the old and obsolete bodily and tacit knowledge and skills into something new. Godkänd; 2007; 20070924 (kirhon)